(untitled) (Research, Society and Development, 2021)
The study intended to characterize the attitudes related to interprofessional collaboration among health professionals in Primary Health Care in a municipality in Maranhão. For this, a cross-sectional study was carried out with 173 health professionals. Questionnaires were applied on interprofessional collaboration, with the Jefferson Scale of Attitudes Related to Interprofessional Collaboration, and on their demographic, educational and professional performance aspects. The data were organized in spreadsheets in Microsoft Excel, as a percentage and analyzed using the Stata version 14. Most of the respondents were female, with an average age of 36.3 years old, community health agent profession. It was identified that the attributes time to practice the profession, time to primary health care and specialization were configured as aspects related to attitudes related to interprofessional collaboration. Our findings demonstrate that Primary Health Care professionals have attitudes related to interprofessional collaboration, and continuing education tools are needed so that collaborative competences are better understood and practiced by these professionals.